Strategi Kampanye Lingkungan Rimba Satwa dalam Konservasi Gajah Sumatera di Provinsi Riau - Habib Alwi Hardanu; Muhammad Firdaus (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The Sumatran Elephant is classified as Critically Endangered and listed under Appendix 1, indicating a high risk of extinction in the near future. The major factor contributing to the decline in the Sumatran Elephant population in Riau is habitat fragmentation due to the conversion of forests into plantations, industrial areas, and settlements. This situation is further complicated by conflicts between elephants and humans along elephant migration routes. The Rimba Satwa Foundation (RSF) is an NGO dedicated to the conservation of Sumatran Elephants and the forests of Riau. Since 2016, RSF has been actively working to raise awareness and knowledge among the public about Sumatran Elephants. This study employs qualitative research methods with descriptive analysis. Informant selection utilizes purposive techniques, and data collection involves interviews, observations, and documentation. Data analysis employs descriptive analysis according to Miles and Huberman. Data validity is ensured through triangulation and prolonged engagement techniques. The study demonstrates that RSF's environmental campaign strategy begins with identifying issues, goals, and audiences. Campaign planning involves audience selection, message formulation, and media selection. Campaign implementation includes public education and habitat conservation. Evaluation is conducted incrementally, from inception to completion, through stakeholder involvement, additional data collection, and assessment of success.